PENANGGULANGAN KRISIS LEGITIMASI HUKUM MELALUI HUKUM PROGRESIF - Agus Muhammad Septiana (Masalah-Masalah Hukum, 2012)
Abstract Practice of law enforcement in Indonesia are degraded to the lowest point in NKRI history. Corruption seems to be a common activity performed by public officials as well as communal done, whether they are sporadic and are structured. Even in some cases, corruption is legalized by the state policy. Law loses its legitimacy as a tool of social engineering. Provide further explanation of how to break the deadlock of law inforcement by Progressive Law in Indonesia, and simultaneously address the crisis of legitimacy of law in Indonesia. That the law can still be accepted by society as an institution where justice must be found, then the law must always be prepared to move in accordance with the changes taking place in society. To implement the action level should be preceded by agreement on the law enforcement component of law enforcement that "pro rakyat" by improving the enforcement of Human Resources. The next action is a growing culture of the welfare of law enforcement and social justice by emphasizing the philosophical and sociological dimensions than merely a normative juridical dimension. In addition, policy makers need to formulate laws and regulations that have a progressive legal substance, the substance of the law in accordance with the values ​​and moral ethics of living in a society that formed the law is the law that berkearifan and conscience. Key words: Progressive Law, Legitimacy of Law, Justice